Changes in musculoskeletal adaptation to physical activity in connective tissue dysplasia: analyzing some triggering factors - M. V. Sankova; V. N. Nikolenko; L. A. Gridin (Спортивная медицина: наука и практика)
Objective: to study pathogenetic homeostasis changes in connective tissue dysplasia to substantiate its role in the predisposition to musculoskeletal injuries.Materials and methods: the basis of this scientific-analytical review was the analysis of data from the electronic portals PubMed-NCBI, Google Academy, and Scientific electronic e-Library.ru.Results: the presented literature review indicates that connective tissue dysplasia, based on polygenically determined and/or environmental factors-induced defects in the synthesis or remodeling of intercellular matrix components, manifested by the formation of deficient connective tissue and significant changes in its biomechanical properties. This is primarily affects the musculoskeletal structure and functions. Depending on the impaired metabolism stage, connective tissue dysplasia is manifested by a variety of clinical signs indicating pathology of skeletal bones and their joints, failure of connective tissue intermuscular layers and tendon-fascial complexes.Conclusions: changes in the musculoskeletal structure and functions are manifested by its initially reduced adaptive capabilities and resistance to physical load, determining the predisposition to injury. A personalized approach to the choice of sports activity and training program in connective tissue dysplasia will help to preserve youth health, prevent re-traumatism and early disability.